Hospital capacity management : insights and strategies - Dick, Robbin; Agness, Robert (Boca Raton, FL : Routledge, 2021)
Hospital Capacity Management: Insights and Strategies details many of the key processes, procedures, and administrative realities that make up the healthcare system we all encounter when we visit theED or the hospital. It walks through, in detail, how these systems work, how they came to be this way, why they are set up as they are, and then, in many cases, why and how they should be improved right now. Many examples pulled from the lifelong experiences of the authors, published studies, and well-documented case studies are provided, both to illustrate and support arguments for change. First and foremost, it is necessary to remember that the mission of our healthcare system is to take care of patients. This has been forgotten at times, causing many of the issues the authors discuss in the book including hospital capacity management. This facet of healthcare management is absolutely central to the success or failure of a hospital, both in terms of its delivery of care and its ability to survive as an institution. Poor hospital capacity management is a root cause of long wait times, overcrowding, higher error rates, poor communication, low satisfaction, and a host of other commonly experienced problems. It is important enough that when it is done well, it can completely transform an entire hospital system. Hospital capacity management can be described as optimizing a hospital's bed availability to provide enough capacity for efficient, error-free patient evaluation, treatment, and transfer to meet daily demand. A hospital that excels at capacity management is easy to spot: no lines of people waiting and no patients in hallways or sitting around in chairs. These hospitals don't divert incoming ambulances to other hospitals; they have excellent patient safety records and efficiently move patients through their organization. They exist but are sadly in the minority of American hospitals. The vast majority are instead forced to constantly react to their own poor performance. This often results in the building of bigger and bigger institutions, which, instead of managing capacity, simply create more space in which to mismanage it. These institutions are failing to resolve the true stumbling blocks to excellent patient care, many of which you may have experienced firsthand in your own visit to your hospital. It is the hope of the authors that this book will provide a better understanding of the healthcare delivery system.
Table of ContentsIntroduction Letter from the AuthorsAbout the AuthorsChapter 1 Hospital Priorities Chapter 2 Bed Assignment Chapter 3 Inpatient and OutpatientChapter 4 Emergency Department Chapter 5 Types of Hospital Beds Chapter 6 Capacity Management Strategies Chapter 7 Discharging Patients Chapter 8 Surgical Short Stay Unit Chapter 9 Hospital Capacity Management Metrics Chapter 10 Complex Care Patients Chapter 11 Integrated Patient Care The PCAT (Patient Centered Admission Team) Efficient Patient Transfer Team-Based CareStandardized Discharge Process An Emergency Department PCAT Model: Hot Zone 30-Day Readmission Discussion and Strategies Chapter 12 Additional Capacity Management Programs (Proceduralist Program)Chapter 13 Discharges before Noon Achieving Discharges before NoonChapter 14 LevelingChapter 15 Ancillary Demand Level StaffingChapter 16 SurgeChapter 17 Starting a Patient Flow Team Chapter 18 Optimal Hospital Operational StrategiesChapter 19 Process ImprovementChapter 20 Conclusion Appendices Glossary Bibliography
OCLC-licensed vendor bibliographic record.
Keywords: Hospital size -- United States; Hospitals -- Administration; MEDICAL / Health Care Delivery; BUSINESS & ECONOMICS / Project Management